2004
DOI: 10.1016/j.jhsb.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Repair and Early Mobilization of the Extensor Pollicis Longus Tendon in Zones 1 to 4

Abstract: We present the results of repair and early mobilization of 100 extensor pollicis longus (EPL) tendon injuries in zones 1 to 4 in 100 patients using a dynamic outrigger splint which controlled metacarpophalangeal joint movements but allowed free movement of the interphalangeal joint. Eighty-two were complete divisions of the tendon and 18 were 80% to 99% tendon divisions. Analysis of measurements obtained routinely at 8 weeks showed 81% excellent and good results using the TAM system. There were 90% excellent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…There may be the potential to increase this range without adverse effects 16,28 and this would be particularly important for repairs in zone TV. 40 Similarly, increased frequency and repetition of active motion is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…There may be the potential to increase this range without adverse effects 16,28 and this would be particularly important for repairs in zone TV. 40 Similarly, increased frequency and repetition of active motion is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hyperextension can often be lost after EPL repair in all injury zones. 3,5,9 According to White's criteria, 17 four of the five patients achieved 'excellent' IP joint extension by eight weeks postoperatively. In reference to Dargan's criteria, 16 two cases achieved 'excellent' and the remaining two 'good' results.…”
Section: Discussionmentioning
confidence: 99%
“…Extensor tendon adherence by scar tissue largely explains the loss of thumb movement after EPL tendon repair. 3,5,9 A hand-based splint allows the wrist to mobilize freely without creating stress on the EPL repair to produce a rupture. The primary function of EPL is IP joint hyperextension, and by positioning the IP joint in hyperextension within the splint, tension is relieved from the distal aspect on the repair itself in zone T II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations